Evolution of the complementary sex-determination gene of honey bees: Balancing selectionand trans-species polymorphisms - Cho, Soochin; Huang, Zachary Y.; Green, Daniel R.; Smith, Deborah R.; Zhang, Jianzhi

(untitled) (Genome Research, 2006)
The mechanism of sex determination varies substantively among evolutionary lineages. One important mode of genetic sex determination is haplodiploidy, which is used by ∼20% of all animal species, including >200,000 species of the entire insect order Hymenoptera. In the honey bee Apis mellifera, a hymenopteran model organism, females are heterozygous at the csd (complementary sex determination) locus, whereas males are hemizygous (from unfertilized eggs). Fertilized homozygotes develop into sterile males that are eaten before maturity. Because homozygotes have zero fitness and because common alleles are more likely than rare ones to form homozygotes, csd should be subject to strong overdominant selection and negative frequency-dependent selection. Under these selective forces, together known as balancing selection, csd is expected to exhibit a high degree of intraspecific polymorphism, with long-lived alleles that may be even older than the species. Here we sequence the csd genes as well as randomly selected neutral genomic regions from individuals of three closely related species, A. mellifera, Apis cerana, and Apis dorsata. The polymorphic level is approximately seven times higher in csd than in the neutral regions. Gene genealogies reveal trans-species polymorphisms at csd but not at any neutral regions. Consistent with the prediction of rare-allele advantage, nonsynonymous mutations are found to be positively selected in csd only in early stages after their appearances. Surprisingly, three different hypervariable repetitive regions in csd are present in the three species, suggesting variable mechanisms underlying allelic specificities. Our results provide a definitive demonstration of balancing selection acting at the honey bee csd gene, offer insights into the molecular determinants of csd allelic specificities, and help avoid homozygosity in bee breeding.